Discrete amplifiable regions (amplicons) in the symbiotic plasmid of Rhizobium etli CFN42. - Romero, D (1995)
Frequent tandem amplification of defined regions of the genome, called amplicons, is a common characteristic in the genomes of some Rhizobium species, such as Rhizobium etli. In order to map these zones in a model Rhizobium replicon, we undertook an analysis of the plasticity patterns fostered by amplicons in the pSym (390 kb) of R. etli CFN42. Data presented in this article indicate the presence of four amplicons in pSym, used for the generation of tandem amplifications and deletions. The amplicons are large, ranging from 90 to 175 kb, and they are overlapping. Each amplicon is usually flanked by specific reiterated sequences. Formation of amplifications and deletions requires an active recA gene. All the amplicons detected are concentrated in a zone of roughly one-third of pSym, covering most of the symbiotic genes detected in this plasmid. No amplicons were detected in the remaining two-thirds of pSym. These data support the idea that most of the known symbiotic genes in this plasmid are located in a genomic region that is prone to the formation of frequent tandem amplification.